Anthracite combustion characteristics and NOx formation of a 300 MWe down-fired boiler with swirl burners at different loads after the implementation of a new combustion system. (1st March 2017) - Chen, Zhichao; Wang, Qingxiang; Wang, Bingnan; Zeng, Lingyan; Che, Miaomiao; Zhang, Xin; Li, Zhengqi
Highlights: Combustion and NO x emissions of the boiler at different loads was investigated. The retrofitted coal/air flow could be all ignited in time at different loads. The fullness degree of coal flame in the furnace at different loads was different. The reheat steam reached the design temperature at middle and low loads after retrofit. NO x reduction of 40% at different loads was achieved with no negative effects. Abstract: A new combustion system has been applied to a 300 MWe down-fired boiler with swirl burners to reduce NO x emissions. The unit provided the introduction of overfire air (OFA) and a decrease in the flow area of the inner and outer secondary air ducts of the swirl burners. Industrial experiments on the retrofitted boiler were performed at different loads. Full-scale measurements of the flue gas temperature distribution in the burner outlet region, the furnace temperature distributions measured by a pyrometer and the local mean gas species concentrations in the region near the sidewall were made at loads of 180, 250, and 300 MWe . The results show that the ignition distance increased with decreasing load, especially as the load decreased from 250 MWe to 180 MWe . At three different loads, the retrofitted coal/air flow could be all ignited in time at a distance in the range of 0.6–1.4 m from the burner outlet. Compared with the original combustion system, the ignition distance of the coal/air flow was significantly reduced at a load of 300 MWe . In addition, at a load of 300 MWe, the temperature of the boiler hopper was much higher than that at loads of 180 MWe and 250 MWe . Compared with the original combustion system, the upper furnace temperature decreased slowly with increasing measurement height at a load of 300 MWe after the retrofit. Measurements of the O2 and CO concentrations in the region near the sidewall indicate that the fullness degree of the coal flame in the furnace at different loads was different. After the retrofit, the reheat steam temperatures reached the design temperature of 541 °C at loads of 180 MWe and 250 MWe, and the average reheat steam temperatures increased by approximately 13 °C. Compared with the original combustion system, a significant NO x reduction (more than 40%) at different loads was achieved without increasing the levels of unburnt carbon in the fly ash.